Rola wątpliwości w filozofii Kartezjusza - Orzechowski, Michał (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
A first impulse to write this article came from noticing, while reading Descartes' "Meditations", that author gives different meaning to the idea of "doubt" in each part of book. In First Meditation "doubt" has a function of a unique method of research, first step to build new, strictly rational and scientific knowledge – in contrast to the former collection of unjustified and un-proved or even false conceptions. Therefore "doubt" has positive value. So why does Descartes in his evidence of God's existence in Third Meditation, talks about "doubt" as if it were imperfection and weakness of human nature? As if it were something worthless and part of "nothingness"? The only way to resolve this contradiction is to consider thoroughly what the role of "doubt" is in each part of "Meditations". Then, it will be clear that in Descartes' "Meditations" problem of knowledge is strictly attached to problem of existence, and how order of cognition changes without notice into cognition of Divine Order.